STRATEGI HOME INDUSTRI KONVEKSI DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA MASYARAKAT KOTA BINJAI (STUDI KASUS ABU BAKAR KONVEKSI MENCIRIM BINJAI TIMUR) - Imsar, Imsar (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2021)
This study aims to determine how the potential and empowerment role of the convection home industry in increasing community household income, and to determine the SWOT analysis of strategies used to increase household income in Binjai city. The background of this research is that in the 2020-2024 RPJMN, one of the macro targets is to improve the processing industry, one of the agendas is to strengthen quality economic defense by encouraging MSMEs. This research method is descriptive qualitative accompanied by a SWOT analysis. The analysis technique used is descriptive method and SWOT analysis, the formulation of a strategy that is processed from the weight of the identification results of the SWOT factor. The results of the calculation of the SWOT analysis of the total IFAS are higher than the total EFAS. The strategy to increase the business of the research object is in cell I Growth is namely the Backward integration or Forward integration strategy. In order to increase its business strength or competitive position, Burn Ash Convection must make efforts to minimize costs and inefficient operations to control the quality and distribution of products.